The research on the surface discharge intensity and its damage to the pressboard in oil-paper insulation under different hydraulic pressures - Guangcai Hu; Daiwen Yang; Jianbing Zhou; Shirong Mou; Qifu Lu; Xinyu Zhu (AIP Advances)
The internal conducting components of power transformers are predominantly insulated by oil and paper, which is vital for ensuring transformers’ safety and reliability. The degradation of oil-paper insulation is primarily induced by discharge, significantly influenced by hydraulic pressure. This study investigates surface partial discharge in oil-paper insulation under varying hydraulic pressures with the help of a novel, self-designed test apparatus. Key discharge parameters were systematically recorded utilizing a commercial partial discharge detector. Findings indicate that both partial discharge inception voltage (PDIV) and breakdown voltage exhibit an increasing trend with increasing pressure, albeit with diminishing rates of increase. Notably, the differential between breakdown voltage and PDIV initially decreases and subsequently exhibits a marginal increase with higher hydraulic pressures. Overall, discharge parameters decrease with increasing pressure, with both average partial discharge values and partial discharge power showing consistent reductions. Surface phenomena and microstructural analyses were conducted to elucidate the structural damage mechanisms induced by discharge. In addition, chemical group and elemental content analyses were performed to infer the underlying principles governing pressboard alterations. These findings provide valuable insights for the operation and maintenance of oil-paper insulated equipment in high-altitude environments and establish a foundation for optimizing the size and weight of oil-paper insulation systems by modulating internal hydraulic pressure in power transformers.